ANALISIS PENCEMARAN LIMBAH BERDASARKAN NILAI RESISTIVITAS - Juandi Juandi M (Jurnal Ilmu Lingkungan, 2009)
Research was conducted to analyze the pollution of waste based on the value resistivity, wherethe relationship is resistivity of BOD and COD at 10 cm depth in the Inlet IPAL PT. RAPPindicates that there is a good correlation between the parameters of waste with a BOD andCOD values resistivity, respectively: BOD = -9.8465 + 552.87 and -645.68 + COD = 18,529.COD has trend greater than the BOD of resistivity for change in other words the presence ofCOD of waste is likely to be greater influence resistivity price. That the value of BOD and CODas a function of depth in the system outlet IPAL PT. RAPP is BOD values are generally smallercompared with the COD value.